MEMBANGUN PENDIDIKAN KARAKTER PESERTA DIDIK DI SEKOLAH - Bhoki, Hermania (STP St. Bonaventura Medan, 2018)
Building educational character is one of the efforts to realize the goals of national education, namely that students develop into human beings who believe and are devoted to God Almighty, have noble character, are healthy, knowledgeable, capable, creative, independent, and become democratic and responsible citizens. Instilling noble moral values (character) in students, starting from the family, continues at school and in society. The family must be a place where children humanize themselves. Schools must be a place where children become aware that they are civilized, love truth, honesty and authenticity. The key to successful character education in schools can be achieved by: preparing moral and religious education; prepare a clear, rational and consistent set of values, rules; input character education in intra, extra and co-curricular activities; teachers, seniors and the academic community are role models for appreciating the value of character education; socialize appropriately, create a conducive learning environment, supported by adequate learning facilities and resources. The community can also be a good role model in instilling character in the younger generation. Synergy between families, schools and communities needs to be built. Building educational character can influence students' thought patterns, actions and actions. Students not only develop intellectually, but can also become human beings with noble character as stated in the national education goals that we must realize